Pelatihan Pemetaan Partisipatif Ekosistem Mangroves di Desa Martajasah Kabupaten Bangkalan - Rachman, Herlambang Aulia; Sari, Alfi Hermawati Waskita; Hidayah, Zainul; Wardhani, Maulinna Kusumo; Hidayati, Nurul; Ahnaf, Hariadi; Indri, Ristrianas (Jurnal Ilmiah Pangabdhi, 2024)
The impact of climate change on coastal ecosystems has been a widely discussed topic in recent decades. The coastal ecosystem that is quite essential is mangroves. Community-based mangrove ecosystem management has actually been carried out in several places, but it is still not optimal. One of the obstacles is that the community cannot understand the spatial or spatial context of the mangrove ecosystem area. Therefore, we tried to carry out community service activities on Participatory Mapping of the mangrove ecosystem based on the local community in Martajasah Village, Bangkalan. The results of this activity are several zones or areas of the mangrove ecosystem determined by the community itself. Some of these zones include cultivation, conservation, and tourism zones. Each zone has its own role and function for the community. It is hoped that the results of this activity can be realized into a book on sustainable mangrove ecosystem management in Martajasah Village, Bangkalan Regency.